TRILOGI EPISTIMOLOGI BAYANI, BURHANI & ‘IRFANI SEBAGAI METODE PENEMUAN HUKUM ISLAM - Ubaidillah, M. Burhanuddin; Risqina, Nur Ayu (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2024)
Sharī'ah law is man-discovered law and not man-made law. Thus it can be understood that the law is not always ready to use, but must be sought and found. Legal discovery is something inherent in every legal system, including Islamic law. The need to find laws is closely related to changes and developments in human civilization. It is often found that there are many events that are not responded to clearly in the text. In mapping epistemological thought, Muhammad 'Abid al-Jabiri in his two works Takwin al-'Aql al-'Arabi and Bunyah al-Aql al-Arabi said that the culture and tradition of Islamic thought in the golden age contained three competing epistemological structures, namely : bayani (explanation), burhani (demonstration) and irfani (gnostic). Bayani epistemology is based on religious texts using a conservative approach. Burhani epistemology uses a philosophical approach, while Irfani epistemology uses a mystical approach. Therefore, this article focuses on the Bayani (Lughawi/Linguistic), Burhani (Ta'lili and Istishlahi) & 'Irfani (Tasawufi/Kasyfi) Epistemological Trilogy as a Method for Discovering Islamic Law with its respective structural patterns along with a brief explanation and example of its application.